A MESOZOIC DINO-FEAST: MULTIPLE TEETH MARKS ON A SAUROPOD DINOSAUR BONE FROM THE UPPER CRETACEOUS OF PATAGONIA AND EVIDENCE ON THEROPOD FEEDING BEHAVIOR - Ariana Paulina-Carabajal; Ariel Hernán Méndez; Karen Ulloa-Guaiquín; Facundo Irazoqui; Yuong-Nam Lee (Publicación Electrónica de la Asociación Paleontológica Argentina)
Marks left by teeth on bones are evidence for inferring trophic interactions. In carnivorous dinosaurs, such evidence is rare in the fossil record. We present here the description of a fragment of sauropod appendicular bone, which exhibits teeth marks consistent with multiple trace makers. The specimen MPM-PV-19111 comes from Cretaceous rocks outcropping at Cerro Fortaleza locality (Cerro Fortaleza Formation, Campanian–Maastrichtian), Santa Cruz Province, Argentina. It preserves three faces, two bearing grooves, and a third bearing shallow pits. There are about 100 scars (we identified at least 99 grooves and 19 pits), with the grooves mainly oriented more or less perpendicular to the main axis of the bone. These grooves have a width ranging from 1 to 3.5 mm, and generally narrow distally. The pits and punctures are circular to subcircular and variable in diameter (1.5–4 mm). The feeding traces are attributable to theropod dinosaurs -abelisaurids and megaraptorids were recorded in the same formation- of mid to large body size, notosuchid crocodyliforms, and a possible indeterminate small mammal.  The teeth marks are considered post-mortem based on the lack of healing on the surrounding bone. The high number of teeth marks suggests both repeated high-power bites in a restricted area (gnawing-like behavior?) and multiple producers, probably biting the bone at different moments since smaller-sized animals would intend to avoid the larger ones. This study aims to describe and interpret the possible origin of the bite marks preserved on this Cretaceous sauropod bone.